Trends in B2C E-Commerce to Enhance Its Accessibility for Older Adults in Greece (Informatica, 2025)
This article explores the adoption of e-commerce among older people, focusing on the importance of information technology and informatics in encouraging this adoption. The study aims to help website designers, businesses, and service providers create effective platforms by exploring e-commerce adoption among older people, identifying barriers to adoption, and variables influencing it. The methodology used in the research design is a qualitative methodology that takes the form of interviews. The study examines the impact of IT services on e-commerce, focusing on developing scalable, secure, and customer-centric IT systems. It also examines factors influencing older individuals' engagement with e-commerce platforms (technological factors and individual characteristics). The research also explores some demographic characteristics of the Greek older population.